“Classification of Ginseng species (Callerya spp) in Lang Giang by molecular mark” - Dong Thi Kim Cuc; Le Thanh Nhuan; Phan Phuoc Minh Hiep; Khuat Huu Trung; Tran Dang Khanh (My University, 2018)
“Classification of Ginseng species (Callerya spp) in Lang Giang by molecular mark”
Keywords: Sâm (Callerya spp); Chỉ thị phân tử; Phân loại loài